2012
DOI: 10.1088/0022-3727/45/48/485302
|View full text |Cite
|
Sign up to set email alerts
|

Formation process and electron-beam incident energy dependence of one-dimensional uneven peanut-shaped C60 polymer studied using in situ high-resolution infrared spectroscopy and density-functional calculations

Abstract: A 3 kV electron-beam irradiation of a C60 film gives rise to formation of one-dimensional (1D) uneven peanut-shaped C60 polymer with a cross-linked structure close to that of the P08 C120 stable isomer obtained from the general Stone–Wales rearrangement. In this study, we examined the evolution of infrared (IR) spectra of C60 films with respect to electron beam (EB) irradiation time, using in situ high-resolution IR spectroscopy and first-principles density-functional calculations, and found semi-quantitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…We proposed that compound 1 is formed from 2 through intermediate 3 (pentaphenanthreno[9,10-a;9',10'-d;9'',10''-g;9''',10'''-j;9'''',10''''-m]corannulene) by the formation of five hexagons, because the formation of an all-sp 2 heptagon by the Scholl reaction was thought to be difficult. [11,18] In fact, we independently confirmed that [6]helicene, ap artial structure of 3,d oes not convert into hexa [7]circulene under the same Scholl reactionc onditions (Scheme 1b). [13] Herein we report new,u nexpected findings discovered during our studyt oi dentify the reaction pathway generating warpedn anographene 1.A sp ossible intermediates for 1,w e have successfully synthesized and characterized two new corannulene-based p-systems containing heptagons (4 and 5), which are different from the originally proposed 3.M oreover, this serendipitous discoveryo fn ew PAHs containingn egative Gaussianc urvatures enabledu st oc ompare the photophysical properties and packing structures of as eries of corannulenebased p-systems containing heptagons.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…We proposed that compound 1 is formed from 2 through intermediate 3 (pentaphenanthreno[9,10-a;9',10'-d;9'',10''-g;9''',10'''-j;9'''',10''''-m]corannulene) by the formation of five hexagons, because the formation of an all-sp 2 heptagon by the Scholl reaction was thought to be difficult. [11,18] In fact, we independently confirmed that [6]helicene, ap artial structure of 3,d oes not convert into hexa [7]circulene under the same Scholl reactionc onditions (Scheme 1b). [13] Herein we report new,u nexpected findings discovered during our studyt oi dentify the reaction pathway generating warpedn anographene 1.A sp ossible intermediates for 1,w e have successfully synthesized and characterized two new corannulene-based p-systems containing heptagons (4 and 5), which are different from the originally proposed 3.M oreover, this serendipitous discoveryo fn ew PAHs containingn egative Gaussianc urvatures enabledu st oc ompare the photophysical properties and packing structures of as eries of corannulenebased p-systems containing heptagons.…”
mentioning
confidence: 56%
“…[5] Examples of heptagon-containing exotic nanocarbonsa re shown in Figure 1a. [6][7][8] The bottom-up organic synthesis of molecular nanocarbons is useful for the construction of various types of nanocarbon materials. Heptagon-containingn onplanar polycyclic aromatic hydrocarbons (PAHs) [9][10][11][12][13] are much less commont han pentagon-containing nonplanar PAHs such as corannulene and its derivatives [4a, 14] (Figure 1b).…”
mentioning
confidence: 99%
“…100 keV and more), C 60 are elastically interacted with incident electrons and thus destroyed to form amorphous carbon [4]. On the other hand, in the case of EB with a low kinetic energy (less than 10 keV), C 60 are inelastically interacted with incident electrons and thus sometimes damaged and sometimes polymerized with each other [5,6]. Besides EB incident energy, the interactions with substrates should be considered for a few C 60 layers [7].…”
mentioning
confidence: 99%
“…In our previous work [6], we examined the evolution of infrared (IR) spectra of C 60 films with respect to EB irradiation time, using in situ high-resolution IR spectroscopy and firstprinciples density-functional calculations, and found semihttp://dx.doi.org/10.1016/j.carbon.2014.09.049 0008-6223/Ó 2014 Elsevier Ltd. All rights reserved.…”
mentioning
confidence: 99%
See 1 more Smart Citation